The distribution of dust in edge-on galaxies: I. The global structure. Issue 4 (31st July 2022) - Mosenkov, Aleksandr V; Usachev, Pavel A; Shakespear, Zacory; Guerrette, Jacob; Baes, Maarten; Bianchi, Simone; Xilouris, Emmanuel M; Gontcharov, George A; Il'in, Vladimir B; Marchuk, Alexander A; Savchenko, Sergey S; Smirnov, Anton A
ABSTRACT: In this first paper in a series we present a study of the global dust emission distribution in nearby edge-on spiral galaxies. Our sample consists of 16 angularly large and 13 less spatially resolved galaxies selected from the DustPedia sample. To explore the dust emission distribution, we exploit the Herschel photometry in the range 100–500 μ m. We employ Sérsic and 3D disc models to fit the observed 2D profiles of the galaxies. Both approaches give similar results. Our analysis unequivocally states the case for the presence of extraplanar dust in between 6 and 10 large galaxies. The results reveal that both the disc scale length and height increase as a function of wavelength between 100 and 500 μ m. The dust disc scale height positively correlates with the dust disc scale length, similar to what is observed for the stellar discs. We also find correlations between the scale lengths and scale heights in the near- and far-infrared which suggest that the stellar discs and their dust counterparts are tightly connected. Furthermore, the intrinsic flattening of the dust disc is inversely proportional to the maximum rotation velocity and the dust mass of the galaxy: more massive spiral galaxies host, on average, relatively thinner dust discs. Also, there is a tendency for the dust-to-stellar scale height ratio to decrease with the dust mass and rotation velocity. We conclude that low-mass spiral galaxies host a diffuse, puffed-up dust disc with a thickness similar to that of the stellar disc.